Realistic operation of two residential cordwood-fired outdoor hydronic heater appliances—Part 2: Particle number and size. (3rd July 2022) - Lindberg, Jake; Vitillo, Nicole; Wurth, Marilyn; Frank, Brian P.; Tang, Shida; LaDuke, Gil; Fritz, Patricia Mason; Trojanowski, Rebecca; Butcher, Thomas; Mahajan, Devinder
ABSTRACT: The use of wood as a fuel for home heating is a concern from an environmental health and safety perspective as biomass combustion appliances emit high concentrations of particulate matter. Wood burning significantly contributes to wintertime particulate matter concentrations in many states in the northern United States. Of particular concern are outdoor wood-fired hydronic heaters. These devices are concerning as they tend to have very large combustion chambers and typical use patterns can result in long periods of low output, which result in an increased particulate matter emission rate relative to high heat output operating conditions. In this study, the performance of two hydronic heaters operating under different combustion conditions, including four different heat output categories approximately corresponding to categories I–IV denoted in Environmental Protection Agency Method 28 Outdoor Wood-fired Hydronic Heaters, and during start-up and reloading events were investigated. Measurements of flue gas particulate number concentration and size for particles with aerodynamic diameters between 0.006 and 10 µm were made using a dilution sampling system. The measured particle number concentration in the flue gas was between 0.71 and 420 million particles per cubic centimeter and was dependent on fuel loading and heat output. For each hydronic heater tested, the highest average particle concentration was found at the beginning of each test during the cold-start condition. Additionally, the majority of the particles had aerodynamic diameters less than 0.100 µm (particles of this size made up between 64% and 97% of all particles) and less than 1% of all particles had aerodynamic diameters greater than 1 µm for all phases. For particles in the accumulation mode, between 0.100 and 1 µm, the mean particle diameter was dependent on fuel loading and heat output. Implications: In this work, we provide information on the particle number concentration and particle size of emissions from outdoor cord- wood-fired hydronic heaters. Wood-fired hydronic heater data is sparsely available compared to wood stove data. Thus, additional data from this source help to inform the work of modelers and policy makers interested in hydronic heaters. The test method used in this work is also novel, as it is more inclusive of real-world use cases than the current certification method. Our data helps to validate the test method and allows for comparisons between real-world use case scenarios, and idealized test cases.